Low-gradient, low-flow severe aortic stenosis with preserved left ventricular ejection fraction: characteristics, outcome, and implications for surgery - Tribouilloy, Christophe; Rusinaru, Dan; Maréchaux, Sylvestre; Castel, Anne-Laure; Debry, Nicolas; Maizel, Julien; Mentaverri, Romuald; Kamel, Said; Slama, Michel; Lévy, Franck (Journal of the American College of Cardiology, 2015)
Severe low-gradient, low-flow (LG/LF) aortic stenosis with preserved left ventricular ejection fraction (EF) has been described as a more advanced form of aortic stenosis. However, the natural history and need for surgery in patients with LG/LF aortic stenosis remain subjects of intense debate. We sought to investigate the outcome of LG/LF aortic stenosis in comparison with moderate aortic stenosis and with high-gradient (HG) aortic stenosis in a real-world study, in the context of routine practice. This analysis included 809 patients (ages 75 ± 12 years) diagnosed with aortic stenosis and preserved EF (≥50%). Patients were divided into 4 groups: mild-to-moderate aortic stenosis; HG aortic stenosis; LG/LF aortic stenosis; and low-gradient, normal-flow (LG/NF) aortic stenosis. Compared with mild-to-moderate aortic stenosis patients, LG/LF aortic stenosis patients had smaller valve areas and stroke volumes, higher mean gradients, and comparable degrees of ventricular hypertrophy. Under medical management (22.8 months; range 7 to 53 months), compared with mild-to-moderate aortic stenosis patients, HG aortic stenosis patients were at higher risk of death (adjusted hazard ratio [HR]: 1.47; 95% confidence interval [CI]: 1.03 to 2.07), whereas LG/LF aortic stenosis patients did not have an excess mortality risk (adjusted HR: 0.88; 95% CI: 0.53 to 1.48). During the entire (39.0 months; range 11 to 69 months) follow-up (with medical and surgical management), the mortality risk associated with LG/LF aortic stenosis was close to that of mild-to-moderate aortic stenosis (adjusted HR: 0.96; 95% CI: 0.58 to 1.53), whereas the excess risk of death associated with HG aortic stenosis was confirmed (adjusted HR: 1.74; 95% CI: 1.27 to 2.39). The benefit associated with aortic valve replacement was confined to the HG aortic stenosis group (adjusted HR: 0.29; 95% CI: 0.18 to 0.46) and was not observed for LG/LF aortic stenosis (adjusted HR: 0.75; 95% CI: 0.14 to 4.05). In this study, the outcome of severe LG/LF aortic stenosis with preserved EF was similar to that of mild-to-moderate aortic stenosis and was not favorably influenced by aortic surgery. Further research is needed to better understand the natural history and the progression of LG/LF aortic stenosis.